"Horror" Genres in Modern Russian Children's Literature. (2nd April 2016) - Sergienko (Antipova), Inna
Abstract : The author investigates the genre of "children's horror"—thrillers and horror written for a young adult readership. The author briefly outlines the evolution of the genre and considers factors that affect the emergence of children's horror fiction in post-Soviet popular fiction for teenagers. She analyzes the main genre categories and the specific nature of the artistic devices that are used. The study focuses on works by Russian authors that were published from the 1990s to the 2010s. To the author's knowledge, this is the first article to study these texts.